The Servier Judgment: The General Court Annuls the Commission's Market Definition but Confirms the Illegality of Certain Patent Settlement Agreements. (22nd February 2019) - Killick, James; Jourdan, Jérémie; Pêcheux, Pierre
Abstract: Judgment of 12 December 2018 T-691/14 Servier SAS, Servier Laboratories Ltd, and Les Laboratoires Servier SAS v European Commission (T-691/14, EU:T:2018:922) The General Court has confirmed that patent settlement agreements entered into between patent owners and manufacturers of generics may be restrictive of competition by object under certain circumstances, while setting aside the European Commission's finding of abuse of dominance and reducing the fine on Servier. The judgment also offers guidance on the effects test under Article 101 TFEU. Given the length of the judgment, this article only covers its main points (for example, issues relating to procedure and fines are not discussed).